2011
DOI: 10.1111/j.1463-1318.2010.02539.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence, treatment and survival of patients with stage IV colorectal cancer: a population‐based series

Abstract: Survival of patients with stage IV CRC has improved over time and this is probably a result of the increased use of chemotherapy and the increased numbers of patients who underwent hepatic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(125 citation statements)
references
References 37 publications
3
117
0
5
Order By: Relevance
“…[1][2][3][4] Studies have reported that >20% of CRC patients present with synchronous metastasis at primary staging. 5 Furthermore, cumulative rates of metachronous liver metastases of 4.3% have been reported at one-year follow-up, increasing up to 14.5% at five-year follow-up. 3 It has been hypothesised that these metachronous liver metastases may in fact develop from occult liver metastases that are already present at the time of primary staging.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Studies have reported that >20% of CRC patients present with synchronous metastasis at primary staging. 5 Furthermore, cumulative rates of metachronous liver metastases of 4.3% have been reported at one-year follow-up, increasing up to 14.5% at five-year follow-up. 3 It has been hypothesised that these metachronous liver metastases may in fact develop from occult liver metastases that are already present at the time of primary staging.…”
Section: Introductionmentioning
confidence: 99%
“…With more than 1.2 million new cases in 2008, colorectal cancer is the third most common form of cancer worldwide (1,2). Nearly 20% of patients are diagnosed at an advanced stage with metastatic disease (1) and over half will ultimately develop metachronous metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 20% of patients are diagnosed at an advanced stage with metastatic disease (1) and over half will ultimately develop metachronous metastases. The recent development of targeted therapies has improved outcomes in patients with advanced colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of CRC was detected at a localized stage is 90.3%. [6][7][8] It is known that approximately half of the CRC diagnosed patients will eventually progress with metastasis. Liver is known to be the most common metastatic site.…”
Section: Ivyspringmentioning
confidence: 99%